The Impact of “Cards in Pairs” Games to The Elementary Student’s Knowledge of Personal Safety Skill for Prevent Sexual Violence in Public Elementary School 2 Serangan - Ni Luh Putu Yunianti Suntari; Ni Nyoman Hartati Hartati; Ida Ayu Rika Kusumadewi Kusumadewi; Ni Kadek Suliani (Babali Nursing Research, 2021)
Introduction: The purpose of this research is to know the effect of “cards in pairs” games to the students’ knowledge of personal safety skill to prevent from sexual violence. Methods: The kind of this research is Pre-Experimental Design with the layout was One-Group Pretest-Posttest used stratified random sampling, with 90 samples. Results: The result of this research showed that the students’ knowledge of personal safety skill before giving the game mostly in the category enough that was 35 people (38,9%) and after giving the game showed that the knowledge of personal safety skill were increase to the students with the most results of the students in the category good that was 69 people (76,7%). The result of this research tested by Wilcoxon test, the obtained value p-value = 0,000<alpha (0,05), then it could be concluded that there was impact by giving sexual education and self-protection from sexual violence with “cards in pairs” games media Conclusion: According the result of the research, it is recommended to the teacher in the school to improve giving the self-protection materials by applying the media “cards in pairs” game, which has an impact on this research.